Utilização de fenos de leguminosas na alimentação de cordeiros Morada Nova em confinamento - Pacheco, Weverton Filgueira (2014)
This study was conducted to evaluate the effects of diets containing different proportions hay of leucaena (Leucaena leucocephala) and gliricidia (Gliricidia sepium (Jacq.) Walp.) on the productive performance, consumption nutrients, quantitative carcass traits, weight and yield and economic viability of the non-carcass components of Morada Nova lambs feedlot. 20 Morada Nova lambs were used, noncastrated, with average weight of 16.36 ± 1.53 kg and approximately 100 days of age. The experimental was a completely randomized design with five treatments and four replications, and the treatments consisted a control diet with 100% of Tifton 85 grass hay as roughage and four diets tested with 50% of Tifton 85 grass hay + 50% leucaena hay, 100% leucaena hay, 50% of Tifton 85 grass hay + 50% gliricidia hay and 100% gliricidia hay. Performance, feed intake, body weight, body weight at slaughter, hot carcass weight, hot carcass dressing, cold carcass weight, cold carcass yield, biological yield, weights of commercial cuts and yield components were not evaluated non-carcass lambs. The use of leucaena and gliricidia hay in animal feed resulted in differences between treatments for performance, feed intake, body weight, body weight at slaughter, hot carcass weight, hot carcass dressing, cold carcass weight, carcass yield cold, biological yield, weights of commercial cuts and income of the non-carcass lambs. According to the study, the hays leucaena and gliricidia can replace Tifton 85 hay in feeding the sheep without harming quantitative carcass traits, providing reduction in food consumption, with improvement in feed conversion and efficiency. Economic projections indicated that the evaluated systems with legume hays were similar when evaluated with Tifton 85 hay for confined sheep with good financial ratios results. The inclusion of leucaena and gliricidia hay proves to be a viable alternative food in the diet of sheep can be used as part of the ingredients in diets for finishing lambs in confinement.